Investigation of the Enthalpy/Entropy Variation and Structure of Cu-Al-Mn-Fe Shape Memory Alloys - Canbay, C. Aksu; Gudeloglu, S.; Genc, Z. Karagoz (Springer/Plenum Publishers, 2015)
Cu-based Cu-Al-Mn-Fe shape memory alloys were produced in an arc melter under vacuum. The crystal structure of the fabricated alloys were determined by means of X-ray diffraction (XRD). The XRD analysis results indicated that the martensitic phase of the samples have an M18R structure. The characteristic transformation temperatures, thermodynamic parameters, and the activation energy values of the samples according to Kissinger and Ozawa methods were determined by differential scanning calorimetry measurements. The austenite transformation temperatures of the samples were found as , respectively. Also, the calculated activation energy values of the samples according to Kissinger and Ozawa methods are compared with each other. The effect of the presence of Al and Fe in the samples on the thermodynamic parameters is studied in this work.
Keywords: Differential scanning calorimetry (DSC); Microstructure; Phase transition; Quaternary alloying elements; Thermal parameters